PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA PLAZA AMANDA JAYA KOTA GORONTALO - Megawati Megawati; Mahludin Baruwadi; Amelia Murtisari (Universitas Negeri Gorontalo, 2016)
This research aims at investigating the influence of service quality towards consumer satisfaction in Amanda Jaya Plaza of Gorontalo City. It applies descriptive quantitative approach through simple regression and correlation test. Data are analyzed by applying SPSS 21 program. Data of this research are primary in which they are in form of questionnaire. Based on finding, it obtains formula of regression of Y = 11,350 + 0,333X which means that quality of service in Amanda Jaya Plaza of Gorontalo City has positive influence to customer satisfaction. Both variables show close and positive relation shown by correlation coefficient that is 0,697. Therefore, coefficient of determination (R2) = 0,485. Fluctuation of consumer satisfaction derives from service quality that is 79,2%, mean remaining 20,8% is influenced by variable which is not explained in this research. Therefore, hypothesis of service quality influences consumer satisfaction in Amanda Jaya Plaza is proved and accepted. Keywords: Service Quality, Consumer Satisfaction